Analysis Of Welding Results On A Pressure Vessel Using Radiography Test Method At PT. DIHI - Hidayahtullah, Muhammad; Wiyono, Slamet (Universitas Sultan Ageng Tirtayasa, 2023)
This research presents the conclusions of the testing conducted at PT. Daekyung Indah Heavy Industry, focusing on the Quality Control process applied to pressure vessels. The Quality Control process involves Non-Destructive Testing (NDT) using the Radiography Test (RT) method. This testing is performed using gamma rays generated by Iridium-192 and applied to a vertical pressure vessel intended to function as a Gas Dehydration Filter. The area under examination is one of the Weld Parts with NC Code on Manhole M1 24 Inch, with SA516-70N material and a thickness of 18 mm, and the entire testing process is conducted with reference to ASME BPVC Section VIII Division I UW-52 as the standard. The test results indicate that out of the 7 areas tested, 5 areas showed indications of defects. Among the 5 areas with defects, there was 1 porosity defect in area A-B and 4 slag inclusion defects in areas B-C, D-E, F-G, and G-A. The repair process required for both types of defects is the removal of the weld groove followed by re-welding until no defects remain in the repaired weld joints.